DIAGNOSTICO FINANCIERO y PROPUESTA DE MEJORAMIENTO EN LA COOPERATIVA DE TAXIS ORILLAS DEL ZAMORA DE LA CIUDAD DE LOJA. PERIODO 2013–2014 - Jima, Bravo Yadira Silvana (2016)
The present thesis work was developed to the Cooperative de Taxis "Zamora banks" from the city of Loja, dedicated to the provision of passenger transportation services, this thesis work carried out with the aim of making the diagnosis understood financial cooperative during 2013 and 2014, to thus help decision-making and proposing viable solutions to the cooperative; to complement the work is has the specific objective such as diagnosing the current situation of the company, determine variations in all periods analyzed, apply indicators and financial reasons, propose an improvement plan that will increase earnings and benefits of members. To complement the work raised specific objectives where will apply indicators and methods of financial analysis that will allow us to determine the financial structure, and drawn up a proposal for improvement in order to contribute to the efficiency of the development of the activities and the quality of business and individual life of each partner. The methodology adopted for the development of the thesis work came from the collection of information provided by the cooperative, from the particular to the general determining shortcomings and knowing the company's activity. In results is the Vertical and Horizontal analysis of the financial statements of the cooperative where financial indicators that are represented in 5 statistical graphics applies, likewise applies a balance which in all periods analyzed there is an unsatisfactory balance because not very significant profits. In the discussion is determined as a result the financial situation of the cooperative where it is known that Working Capital is $12.732.47; for every dollar it owed the cooperative has $1.01 to solve unforeseen, in regard to solidity is obtained the 0.0066; In indebtedness 0.66 is generated and finally sees that 10% exist in yield on assets and the return of heritage to shareholders. The conclusions and recommendations that were based on financial diagnosis determines that the Cooperative de Taxis "Shores of the ZAMORA" has its debt at a normal level, so also there are expenses that exceed the quota provided by partners which would be essential to do one projection of costs and thus give priority to the most relevant expenses.